ANALISIS RESPON MAHASISWA FKIP UNIVERSITAS JEMBER TERHADAP KERUSAKAN FUNGSI SUNGAI DAN DAMPAK YANG DITIMBULKANNYA - Yunita Sari Ayundah Diniarti (Universitas Pakuan, 2021)
The activity of disposing of waste and other polluting items into the river pollutes the river and has a big impact on living things. The inappropriate use of the river causes damage to the function of the river. This problem cannot be resolved in a short time, it takes self-awareness of each community to overcome these problems. As a student who is considered a young man who can make changes to the nation, each student should feel sympathy and an effort to spark ideas for solving the problems above. However, in fact there are not many students who have good responses to the above problems, so a study is needed to see the extent to which students respond to these problems. The purpose of writing this article is to find out how the 3rd semester students of Jember University respond to the damage to the function of the river and its impacts. This study used the subjects of several FKIP students, University of Jember semester 3, batch 2019. The above research was conducted using quantitative and qualitative methods. The results showed that the response of the students regarding the damage to the function of the river and the impacts it caused was quite good which can be seen from the high percentage value found in the table of the results of the description of student responses on indicators two to four. However, in the first indicator there are still deficiencies in student responses to innovations in preventing damage to river functions.